Tax Officer Services and Tax Justice as Preventive Action for Tax Evasion - Dewi Rachmania, Eni Suharti, (Jurnal Akuntansi, 2019)
The research is aimed to analyze of reduction of tax evasion case. Where, this effort by implementation service courtesy of tax officer/Fiscus and fairness of tax regulation for corporate as tax-payer. This matter caused by many tax-fraud that have done by tax-payer (small and big enterprise). Generally, these cases have influence to un-performing tax revenue of government. The tool used in this research is the structure equation model (SEM) with partial least square (PLS) alternative approaches. PLS evaluation model is done by assessing outer model and inner model. That used to test 98 samples (respondent) obtained from the slovin’s formula. The result of this reseach show indicates that the implementation of tax officer services/Fiscus have negative impact partially to tax-evasion and fairness of tax regulation has not effect partially on tax evasion.